Analisis Manajemen Risiko Keamanan Sistem Pengolahan Data Accurate Menggunakan Metode OCTAVE-S - Butar, Fajar Rido Butar; Saputra, Eki; Marsal, Arif; Hamzah, Muhammad Luthfi; Fronita, Mona (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
PT.XYZ is a palm oil company currently implementing the Accurate data processing system to manage data at its factory. This system is utilized for weighing incoming palm fruit, processing palm fruit within the factory, and generating various reports. However, during the implementation process, the system has encountered several threats that have had an impact on the company. These threats include connection errors, human errors, and server downtime. To address these issues, a threat risk analysis is necessary to minimize the likelihood of similar problems occurring in the future. In this study, the OCTAVE-S method is employed as it offers solutions for managing other threats. The risk analysis results indicate that there are six security practices that pose a high risk to the company's system security. These practices are IT Security Monitoring and Audit, Authorization and Authentication, Vulnerability Management, Encryption, Security Planning and Architecture, and Incident Management. Based on these findings, it is recommended that the company conducts a review of its security practices to prevent the emergence of new risks that may affect its business processes.